Putting "the system" into a school autonomy reform: the case of the Independent Public Schools program. Issue 1 (2nd January 2016) - Gobby, Brad
Abstract : The Australian Federal and state governments have been introducing neoliberal reforms to the governance of their education systems for a number of decades. One of the most recent programs of reform is the Western Australian Independent Public Schools (IPS) initiative. Similar to decentralizing reforms around the world, the IPS program seeks greater school autonomy from the state education bureaucracy by providing selected principals and school communities with a range of responsibilities. This paper seeks to better understand the kind of post-welfare form of government IPS enacts. Using concepts from the governmentality literature, this paper analyses documents related to the program, and interview data collected from key government officials responsible for the initiative. It finds that while IPS renders operable a neoliberal critique of the public sector by implementing the processes of contractualization, it also diverges from the ideal schema of neoliberalism. Analysis reveals that a number of strategic, pragmatic and political concerns have resulted in what some may view as a contradictory rationality of "the system" being instituted as a key element in this autonomizing reform. The paper calls for attention to the actual operationalizing of neoliberal reform projects to gain a nuanced understanding of modern regimes of rule.